Tax Fraud: Precedent criminal activity for money laundering? - Yerovi B., Ernesto (2023)
The purpose of this article is to investigate the crime of money laundering, this kind of crime has a directly relationship with the crime on tax fraud. Internationally, this crime has been recognized and classified on its revolution and history. This evolution is responsible that the laws of each State have intensified the penalties, governing verbs and active subjects of the crime. The different articles have many similarities; and, processes to try to impute criminal responsibility to presumed active subjects such as lawyers in the exercise of their profession by allegedly charging professional fees that are the product of illegal activities, or, to the Treasury fraudster to whom it is intended to impute the crime of laundering justified in the existence of antecedent criminal activity. With this information, it will be of vital importance to carry out a general analysis, based on the criminal history, criminological positions, criminal policy, legislation and jurisprudence in order to reach a conclusion about whether it is correct or incorrect to impute and recognize as active subject to the tax fraudster.The answer to this question will be made in a motivated way through the development of this research work